2021
DOI: 10.1111/rec.13330
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative spread is key to applied nucleation success in non‐native‐dominated grasslands

Abstract: Applied nucleation (i.e. planting vegetation patches) is a restoration strategy that better recreates natural ecosystem heterogeneity and requires fewer resources compared to planting the entire area. Whereas applied nucleation shows promise as a forest restoration strategy, this approach has received little study in grassland restoration, where the spread of planted vegetation nuclei may be impeded by aggressive non-native species. We compared the establishment and cover of restored native grass, forb, and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
2
0
3
Order By: Relevance
“…As hypothesized, native and non-native recruitment were significantly lower in both NM and NNM plots compared to control plots, which has been seen in other restoration studies using mulch, such as those in grassland habitats (Holl et al 2021). While some studies have shown that certain instances of mulch removal negatively affected native cover and richness (Kimball & Schiffman 2003), our results are congruent with studies that show reduced establishment of native and nonnative species with mulch addition (White et al 1995;Concilio 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As hypothesized, native and non-native recruitment were significantly lower in both NM and NNM plots compared to control plots, which has been seen in other restoration studies using mulch, such as those in grassland habitats (Holl et al 2021). While some studies have shown that certain instances of mulch removal negatively affected native cover and richness (Kimball & Schiffman 2003), our results are congruent with studies that show reduced establishment of native and nonnative species with mulch addition (White et al 1995;Concilio 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding plant growth, we hypothesized that NNM would negatively impact native species due to potential allelopathic effects (Oduor et al 2020), while NM would increase native growth due to increased soil moisture and decreased competition with non-natives (Benigno et al 2012). We also hypothesized that the implementation of both NM and NNM would increase soil moisture while decreasing seedling recruitment (Holl et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, moss may also serve as seed traps, as shown in peat bogs and peatlands where this group of plants is recommended for restoration (Groeneveld et al 2007). Planting nurse plants has been applied and evaluated in different open ecosystems (see Castellanos et al 1994 and Rubio‐Casal et al 2001: saltmarshes; Hulvey et al 2017: dryland in general, “restoration island”; Franks 2003: “coastal dunes”; Holl et al 2021: planting patches, “applied nucleation”) and may lead to the establishment of “islands of fertility” (Gornish et al 2021) where vegetation development is facilitated. However, the use of nucleation‐based techniques in the restoration of grasslands is still little explored (Shaw et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A menudo, la nucleación se encuentra referida en la literatura científica como una técnica o estrategia de RE. Autores como Boanares y de Azevedo (2014), Bechara et al (2016) y Corbin et al (2016) parecen considerarla una técnica, mientras que Corbin y Holl (2012) y Holl et al (2021) la clasifican como una estrategia. La nucleación es una técnica empleada para superar barreras relacionadas con la dispersión y el establecimiento (Vargas et al 2007; Lindig-Cisneros 2017); dentro de la restauración asistida, puede ser el eje central o formar parte de una estrategia junto con otras acciones.…”
Section: La Nucleación Como Técnica De Restauración Ecológicaunclassified
“…En el caso específico de la nucleación aplicada, se estableció que los beneficios no solo incluyen la atracción de dispersores y la facilitación del reclutamiento de otras plantas, sino que los núcleos sirven como áreas focales de colonización donde hay mayor heterogeneidad del hábitat para diversos organismos (Zahawi et al 2013;Holl et al 2013;Bechara et al 2016;Hulvey et al 2017). Otros beneficios en ambientes degradados como las pasturas son la provisión de sombra para suprimir el crecimiento de heliófitas dominantes (Holl et al 2021) y la exportación de semillas desde los núcleos a sitios inmediatos con baja regeneración (Reis et al 2010;Wilson et al 2021). Cabe destacar que, según el contexto específico, la nucleación tiene el potencial de lograr metas de restauración a un costo menor que estrategias como las plantaciones forestales tradicionales (Holl et al 2020;Bechara et al 2021;Wilson et al 2021).…”
Section: Beneficios De La Nucleación Y Desventajasunclassified